XPO1 serves as a prognostic marker involving AKT/MAPK/TGFBR1 pathway in OSCC - Ying Han; Ying Peng; Haofeng Xiong; Liujun Zeng; Tianyi Zhang; Kun Xia; Xin Hu; Tong Su (Cancer Medicine, 2024)
Abstract Background Exportin 1 (XPO1) is a nuclear export protein that facilitates the transportation of various substances. XPO1 promotes tumor development as a poor prognostic factor in a variety of tumors and is a therapeutic target for screening inhibitors. However, the role of XPO1 in oral squamous cell carcinoma (OSCC) has yet to be determined. Methods The expression patterns of XPO1 mRNA in OSCC were investigated using bioinformatics tools, and the expression levels of XPO1 protein in OSCC specimens were confirmed by immunohistochemical assays. Survival analysis was conducted to evaluate the impact of XPO1 on prognosis. GO and KEGG enrichment analyses were utilized to uncover the signaling pathways mediated by XPO1. Additionally, we examined the association between XPO1 and AKT/MAPK/TGFBR1 and immune infiltration. Results XPO1 mRNA and protein expression levels were significantly enhanced in OSCC and associated with OSCC severity. Enhanced XPO1 expression was indicative of poor survival. Functional analysis showed that XPO1 mediated pathways associated with cell cycle and DNA replication and reduced immune infiltration in OSCC. Additionally, XPO1 mRNA and protein expression levels had significant positive relationships with AKT/MAPK/TGFBR1. Conclusions XPO1, as a marker of poor prognosis in OSCC, can promote OSCC through AKT/MAPK/TGFBR1.